Sentimen Investor, Faktor Fundamental Makroekonomi dan Excess Return Pasar Saham di Indonesia - Lestari Ayu Angraini; Novita Sari Hutasoit; Gracia Shinta Ugut (University of Merdeka Malang, 2022)
This study aims to examine the effect of investor sentimen and macroeconomic fundamentals on excess returns which are useful for decision making in optimizing portfolios. This study used the aggregate market with the aim of knowing the entire stock market in Indonesia, and used daily data during 2020 with a total of 242 data according to the number of trading days in 2020. This study used trading volume, advance-decline ratio, market turnover, share turnover for sentiment investor indicators. SBI Interest Rate, SP500 Index, and exchange rate were used as indicators of macroeconomic fundamentals. The sentiment investor proxies are analyzed using Principal Component Analysis (PCA). Through GARCH analysis, it is found that investor sentimen has a positive effect on excess return. Based on the Granger Causal test, the study found that excess return granger cause investor sentiment, but not vice versa. Regarding macroeconomic factors, it can be concluded that macroeconomic variables, namely interest rates, the US SP500 index, and exchange rate have a simultaneous effect on excess return, where the macroeconomic variables explain 22,64% excess return in the Indonesian stock market.